What shapes the intraspecific diversity of vegetables: A case study of pumpkin in Northern Vietnam - Nguyen, Thi Phuong; Struik, Paul C.; Almekinders, Conny J. M.; Swaans, Kees; Vu, Thanh Hai; Stomph, Tjeerd-Jan (2024)
Home grown vegetables are the main source of nutrition diversity for smallholder farmers and they provide resilience to shocks and stresses in nutrition access. Seed is a key input to ensure this home growing of vegetables, whether from local or external source. The influx of external seed, rapid development of output markets and a high rate of land fragmentation pose strains on local diversity and make farmers more dependent on external seed sources and fluctuation of markets’ demands. This study aimed to elucidate the roles of exogenous seed influxes and output markets in temporal and spatial dynamics of intraspecific diversity of pumpkin, a culture-linked crop, in Northern Vietnam. Interviews with 210 farmers, 32 seed and fruit vendors/companies, and 8 key-informants (researchers and extensionists) were held in 2021-2022. Bayesian inference and social network analysis were employed to trace the dynamics of cultivar diversity at household, village and landscape levels and the seed flow from seed providers to farmers. Per household three cultivars were grown on average and allocated to specific ecological locations, which were decided based on use value (income generating, home and/or livestock food sources), land availability, and companion crops (e.g., orchards and maize). The diversity of local cultivars was reduced where the crop had a weaker cultural (culinary and between-generations) tie, when the introduced cultivars were preferred by output markets, when land was limited, and when it was not an important food source. The adoption of new cultivars was linked to the presence of seed vendors and output markets. In addition, this adoption has been accelerated in the recent decade, and notably in the Covid-19 pandemic time when storable fruits were in high demand, returning a good income to farmers. Nevertheless, the volatility of the product price also posed a risk on investments in vegetable production to farmers. Meanwhile, the maintenance and/or resumed use of the local cultivars was supported by the informal seed distribution and social networks, but varied among farmer communities. Therefore, we suggest that there is a need, to sustain local seed distribution networks, simulate exogenous seed influxes, strengthen local associations among farmers and seed/output vendors, and support farmers in keeping track of emerging demands in output markets, to develop sustainable vegetable food sub-systems for local farmers. Key words: smallholder farmers; vegetable food; diversity; markets.